2016
DOI: 10.1007/s12039-016-1156-3
|View full text |Cite
|
Sign up to set email alerts
|

Why are Hydrogen Bonds Directional?

Abstract: The recent IUPAC recommendation on the definition of hydrogen bonding points out that directionality is a defining characteristic of a hydrogen bond and the angle ∠X-H-Y is generally linear or 180 •. It also suggests that the X-H• • • Y angle be greater than 110 • for an interaction to be characterized as a hydrogen bond but does not provide any rationale for the same. This article reports a rationale for limiting the angle, based on the electron density topology using the quantum theory of atoms in molecules.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 43 publications
3
26
0
1
Order By: Relevance
“…Results confirmed that all donors present rather similar directional propensity, with minor variations across the set (Supplementary Fig. S5) and in agreement with previous reports 35,50,51 . Acceptors, on the other hand, were found to be anywhere from nearly isotropic to very directional (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Results confirmed that all donors present rather similar directional propensity, with minor variations across the set (Supplementary Fig. S5) and in agreement with previous reports 35,50,51 . Acceptors, on the other hand, were found to be anywhere from nearly isotropic to very directional (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, these results challenge the established consensus according to which strength and directionality are correlated, with the latter depending on the former. Therefore, strong acceptors are expected to be more directional 35,45,[52][53][54] , and weak ones less so 35,45,54,55 . When quantifying directionality of acceptors and donors separately, we found no such correlation with acceptor strength For example, in the same molecular context, sulfur shows more directional character than oxygen, despite the former being a weaker acceptor (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim here is to find an interpretation of the directionality and strength of the hydrogen bond by correlating the orientation of the lone pair and the corresponding MESP minimum value. According to the recent IUPAC recommendation, directional preference is a defining characteristic of the hydrogen bond …”
Section: Introductionmentioning
confidence: 99%
“…According to the recent IUPAC recommendation, directional preference is a defining characteristic of the hydrogen bond. [28,[34][35][36] The lone-pair-bearing molecules such as amines and carbenes show electron donating tendency toward the CO 2 molecule and significant research has been conducted on using polyamines as potential CO 2 capturing agents. [37][38][39][40][41][42] Keeping this in view, we also study the intermolecular complexes of lone-pair-bearing molecules with CO 2 and investigate the structural and energetic features of these complexes in relation with the features of the lone pairs.…”
Section: Introductionmentioning
confidence: 99%